PENGARUH PROFESIONALISME, KOMITMEN ORGANISASI, LOCUS OF CONTROL, DAN ETIKA PROFESI TERHADAP KINERJA AUDITOR INTERNAL PADA PERGURUAN TINGGI DI KOTA BANDA ACEH DAN ACEH BESAR - Anisa Syarifah; Nita Erika Ariani (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study aims to (1) determine the effect of professionalism on the performance of internal auditors. (2) Knowing the effect of organizational commitment on the performance of internal auditors. (3) Knowing the effect of locus of control on the performance of internal auditors. (4) Knowing the effect of professional ethics on the performance of internal auditors. (5) Knowing the effect of professionalism, organizational commitment, locus of control and professional ethics on the performance of internal auditors. The population of this research is 40 internal auditors who work at universities in Banda Aceh and Aceh Besar. This research is a research that uses primary data with data collection techniques obtained from distributing questionnaires. Sample selection is done by saturated sampling. The analytical method used is multiple linear regression. Statistical testing was carried out with the help of the SPSS version 22 application. The results showed that professionalism, organizational commitment, locus of control, and professional ethics had an effect on the performance of internal auditors.